Legal and institutional framework for pollution prevention in Malaysian rivers - Syed Abdul Kader, Sharifah Zubaidah; Mustafa, Maizatun (LexisNexis, 2008)
The paper examines the legal and institutional framework of powers relating to pollution prevention in rivers. Federalism in Malaysia has resulted in powers over pollution control in rivers being held by several agencies and authorities. The Drainage and Irrigation Department ('DID') have a privotal role by virtue of the Ministerial Functions Act, 1969 that grants to this department jurisdiction over river conservation. However in the exercise of such functions, there are a host of other functions that do not come within the purview of the DID but directly affect the water quality of rivers. Examples include licensing of industries, sand-mining, pig-rearing, cattle rearing; sewerage services, disposal of effluents and the eviction and resettlement of squatters. These matters come within the jurisdiction of local authorities, Sewerage Services Department, Department of Environment and the District Land Office respectively. Are there overlapping of powers in this scenario? Is there a need to resolve them through an integrated approach? After examining relevant legal provisions, this paper looks at several existing models of river management and points out that other than the existing legal and institutional framework at macro level, effective pollution control of rivers depends very much on local 'on th ground' factors such as the type of rivers, its functions, the interest of local stakeholders and political will. The paper then proposes several alternatives for a more efficient river management framework towards better pollution control and improved water quality in Malaysian rivers.